Density and composition of macroinfauna in three selected areas in Southern Negras Occidental. - Catalan, Rae Joy Alipo-on
The macrobenthic fauna of Hinigaran, Binalbagan and Himalayan, southern Negros Occidental was investigated in this study as part of the dredge survey for the studies on the biology and fishery of the short-necked clam Paphia undulata. The sediment samples were collected during the oceanographic cruise on May 23, 2008 from 20 permanent dredge stations using a Van veen grab sampler and a corer., A total of 27 taxa were identified with mean density of 2,478.74 ind m raised to negative 2. The most abundant taxa were Polychaeta, Nematoda and Sipuncula. The relationships of macrofaunal density with dept, grain size (sediment type), sorting index, percent sand and percent silt were determined.